The Viability of Glycine Fermentation in Titan’s Subsurface Ocean - Antonin Affholder; Peter M. Higgins; Charles S. Cockell; Catherine Neish; Krista M. Soderlund; Michael J. Malaska; Kendra K. Farnsworth; Rosaly M. C. Lopes; Conor A. Nixon; Mohit Melwani Daswani; Kelly E. Miller; Christophe Sotin (The Planetary Science Journal)
Energy and nutrient sources for life could be delivered to Titan’s subsurface water ocean from both its surface above and its core below. Organic matter forming de novo in Titan’s atmosphere and depositing on the surface may hydrolyze upon descent into the ocean with impact-generated melt pools sinking through the ice, adding to a primordial inventory released by the core during differentiation and/or across geologic time. This raises the possibility that abiotic organic carbon could fuel heterotrophic carbon assimilation into biomass in Titan’s ocean if it is inhabited. Glycine fermentation is one possible metabolism of interest, because mechanisms exist to transport glycine to Titan’s ocean and anaerobic fermentations do not rely on additional strong oxidants which may not be present on Titan. Using bioenergetic modeling, we show that while conditions favorable to glycine fermentation may exist, they are highly dependent on temperature. Additionally, the ability of that metabolism to fuel a global biosphere is limited by the slow delivery of glycine by impact melt pools (<10 nmolal yr ^−1 optimistically, with a >1 mmolal primordial component). A total population of 10 ^14 –10 ^17 cells (a few kilograms of carbon) can be sustained, amounting to less than 1 cell kg ^–1 water when diluted through the entire ocean. Constraining notionally detectable biospheres on Titan will therefore require (i) considering localized environments that may concentrate cells, (ii) better characterizing other candidate metabolisms (e.g., degradation of acetylene or polyaromatic hydrocarbons) for quantitative bioenergetic modeling, and (iii) resolving new mechanisms to deliver organics and oxidants for life.